2021
DOI: 10.18196/jerss.v5i2.11339
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Unemployment Rate, RMW, and HDI on Poverty Rates in the Special Region of Yogyakarta

Abstract: Poverty is one of the most complex problems in a country's economy, including in a region. Therefore, efforts to reduce poverty must be carried out comprehensively. The purpose of this study was to analyze the effect of the unemployment rate, the Regional Minimum Wage (RMW), and the Human Development Index (IPM) on the poverty rate in the districts of Bantul, Sleman, Gunung Kidul, Kulon Progo, and the City of Yogyakarta in 2015-2019. The analytical method used is panel data regression random effect models (REM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…The probability value is 0.0083, and the coefficient value is -3.068771, meaning the probability value is smaller than 0.05. Studies by Alhudhori (2017); Oktaviani &A'yun (2021) andSuripto &Subayil (2020), corroborate this finding and show that HDI has a significant effect on poverty; however, research by Leonita & Sari (2019), takes a different stance and states that HDI does not affect poverty. The findings of this study are consistent with the views of Arsyad (2016), who observed that the best way to combat poverty is through the development of human resources, as qualified human resources are more likely to find employment.…”
Section: Discussionmentioning
confidence: 92%
“…The probability value is 0.0083, and the coefficient value is -3.068771, meaning the probability value is smaller than 0.05. Studies by Alhudhori (2017); Oktaviani &A'yun (2021) andSuripto &Subayil (2020), corroborate this finding and show that HDI has a significant effect on poverty; however, research by Leonita & Sari (2019), takes a different stance and states that HDI does not affect poverty. The findings of this study are consistent with the views of Arsyad (2016), who observed that the best way to combat poverty is through the development of human resources, as qualified human resources are more likely to find employment.…”
Section: Discussionmentioning
confidence: 92%
“…Kondisi tenaga kerja yang sehat, tingginya pengetahuan dan memperoleh penghidupan yang layak, maka output yang dihasilkan semakin baik dan berkualitas [11]. Hal ini sejalan dengan penelitian terdahulu yang menunjukan IPM berpengaruh negatif signifikan terhadap jumlah penduduk miskin di Indonesia tahun 2011-2015 [12], penelitian serupa menujukan bahwa IPM memiliki hubungan korelasi negatif dan memiliki pengaruh terhadap kemiskinan di provinsi DIY 2015-2019 [13], dan penelitian serupa juga menunjukan IPM berpengaruh negatif signifikan terhadap kemiskinan [14] [15].…”
Section: Pembahasanunclassified
“…Upah minimum regional mempengaruhi tingkat kemiskinan. Upah minimum yang mempengaruhi kemiskinan dikarenakan biaya sosial dari inflasi yang memberikan orang-orang sekitar berdampak menjadi miskin (Oktaviani & A'yun, 2021).…”
Section: Upah Minimumunclassified
“…Upah Minimum Kabupaten/kota di Provinsi Yogyakarta berkoefisien regresi sebesar 78.15547 sehingga dapat dijelaskan bahwa upah minimum di Provinsi Yogyakarta memiliki pengaruh terhadap kemiskinan di Provinsi Yogyakarta. Dalam Penelitian (Oktaviani & A'yun, 2021) menjelaskan bahwa kenaikan tingkat upah minimum kabupaten/kota dapat menaikkan pendapatan masyarakat contohnya di Provinsi Yogyakarta sehingga meningkatkan kesejahteraan masyarakat sekitar dan memberikan dampak yang baik di lingkungan sekitar dengan berkurangnya jumlah penduduk yang miskin. Sesuai dengan penelitian (Islami & Anis, 2019) mengatakan upah minimum berdampak positif terhadap tingkat kemiskinan.…”
Section: Uji Kebaikan Model Terpilih Uji Eksistensi Model (Uji F)unclassified